PENGGUNAAN MINYAK SOLAR DAN SINAR SURYA PADA PENGOVENAN TEMBAKAU VIRGINIA - SAMSURI TIRTOSASTRO; ABI DWI HASTOMO; SOEBANDI SOEBANDI; DARMONO DARMONO (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
The use of diesel-oil and solar energy as an alternative energyfor Virginia tobacco curingThe use of diesel oil and solar energy in the curing on Virginia tobacco was studied in two steps, i.e., the laboratory experiment al Ihe Research Institute for Tobacco and fiber Crop Malang and ield experiment (economic scale) in East Lombok, NIB. The study was conducted from July to September 1998. The laboratory experiment was aimed at evaluating the effect of diesel oil on (he aroma of cured leaves. Results showed that there was no Strange aroma of Ihe cured-leaves, as the effect of diesel-oil burning Ihe experiment using economic scale curing-bani indicated that the diesel-oil consumption was 0 76 l/kg krosok and if flat-plate solar collector was constructed as a roof, consumption decreased 7.84% which was equal with 0.06 l/kg krosok or 2.574 kJ/kg krosok. Economic analyses showed that using diesel-oil and flat-plate solar collector as a energy source gave a proit chance and an ability to pay the 18%/year of the capital interest, with B/C ratio -1.74, NPV=Rp 45 340 131, and IRR-52 93%. If only diesel-oil was used, it gave a lower proit with B/C ratio=l.77, NPV=Rp 46 425 215. and IRR=53.19%. The increase in the diesel-oil price up to Rp I 500/1 would give a profit chance and an ability lo pay the capital interest, with the B/C ratio = 1.487 and 1 .490. with IRR = 52.67% dan 52 99%, for curing the tobacco leaves with diesel-oil and solar collector, and with diesel-oil only, respectively.